Lifestyle Interventions Improving Cannabinoid Tone During COVID-19 Lockdowns May Enhance Compliance With Preventive Regulations and Decrease Psychophysical Health Complications - Brugnatelli, Viola; Facco, Enrico; Zanette, Gastone (Frontiers in Psychiatry, 2021)
Studies investigating the psychosomatic effects of social isolation in animals have shown that one of the physiologic system that gets disrupted by this environment-affective change is the Endocannabinoid System. As the levels of endocannabinoids change in limbic areas and prefrontal cortex during stressful times, so is the subject more prone to fearful and negative thoughts and aggressive behavior. The interplay of social isolation on the hypothalamic-pituitary-adrenal axis and cannabinoid tone triggers a vicious cycle which further impairs the natural body’s homeostatic neuroendocrine levels and provokes a series of risk factors for developing health complications. In this paper we explore the psychosomatic impact of prolonged quarantine in healthy individuals, and propose management and coping strategies that may improve endocannabinoid tone, such as integration of probiotics, cannabidiol, meditation and physical exercise interventions with the aim of supporting interpersonal, individual and professional adherence with COVID-19 emergency public measures whilst minimizing their psycho-physical impact.